A Smart Method for Monitoring and Scheming Of Road Luminosity Using GSM Equipment - Ravichandran G; Krishnamurthy M (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In our modern life, energy wastage in Streetlight is a big problem faced in walkways and roads during dawn and dusk. These days, the present road light structures are wired which are hard to make and has poor adaptability. During the daytime, the battery gets charged by sun rays, and the energy can be used to power the road lights at night time. The structure regards sun situated cell foundation. It is like manner delineates the usage of remote sensor frameworks using GSM for streetlight checking and control. This system would give remote access to streetlight upkeep and monitoring. It likewise talks about a perceptive framework that takes programmed choices for sparkling control (ON/OFF/DIMMING) considering encompassing light power and time both at a similar minute. The data collected from the sensor is given to the microcontroller of one unit, and at the same time, the SMS is sent through GSM to the Raspberry PI microcontroller to monitor and control the street light.